William Styron - American Writers 98 : University of Minnesota Pamphlets on American Writers - Pearce, Richard (Book collections on Project MUSE., 1972)
William Styron - American Writers 98 was first published in 1971. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.